Proposição de metodologia baseada em indicadores de qualidade do solo para sustentabilidade da produção agrícola - Batista, Núbia Lais Fernandes (2016)
The global expectation concerning the population growth leds to an increase of food production needs around the world. Furthermore, sources of stress has been created over the environment, especially related to soil degradation and water scarcity, which has been raising concern of soil quality and sustainability of agricultural production over the last decades. In Brazil, it is necessary to develop strategies for land use planning in order to minimize the impacts of erosion processes and to ensure sustainable agricultural production. In this sense, conservation methodologies using soil quality indicators that can be applied at a basin scale have been widely used. So, this work proposes a methodology to evaluate the impacts associated to land use and occupation and agricultural management using the "TPS-PS" indicator, estimated by subtracting the soil loss rate (TP) from the soil loss tolerance (TPS), wich was applied to a region of interest of the pilot hydrographic basin (Córrego do Sossego in Itarana/ES - 65 km²). Using the Soil and Water Assessment Tools (SWAT) model to simulate alternative scenarios of land use / agricultural management / type of crop for the basin, it was possible to: diagnose the current levels of soil loss (PS) and its associated TPS-PS indicator for each part of the basin; verify the resultant soil loss (PS) levels and its associated TPS-PS indicator for each region of the basin in which an alternative land use / agricultural management / crop type scenario was adopted. The scenarios was participatively defined in a workshop involving regional rural producers and experts from the State Agricultural Agency, as well as information on the natural susceptibility to soil erosion. The use of the proposed methodology alowed a significant reduction of the soil loss rate, contributing to achieve the goal established in this study that was to reduce sediment production in the basin. The performance of the proposed methodology was satisfactory since, through the TPSPS indicator, it was possible to diagnose the critical condition of the studied basin concerning the erosive processes, to propose alternatives for soil conservation, enabling the involvement of the local community and the integration of knowledge.